Genetic Evidences of Biosurfactant Production in Two Bacillus subtilis Strains MB415 and MB418 Isolated From Oil Contaminated Soil - Yasmin, Azra; Aslam, Fozia; Fariq, Anila (Frontiers in Bioengineering and Biotechnology, 2022)
Biosurfactants are a diverse group of amphiphilic compounds obtained from microbes. In the present study, the genomic analysis of biosurfactant-producing Bacillus subtilis MB415 and MB418 obtained from oil-contaminated soil was performed. Initially, the strains were screened for biosurfactant production by hemolytic assay, emulsification index, and oil displacement. Further FTIR analysis of extracted biosurfactants revealed the presence of lipopeptides. The sequenced genomes of MB415 and MB418 were of 4.2 Mbps with 43% GC content. Among more than 4,500 protein-coding genes, many were involved in virulence, metal/multidrug resistances, flagella assembly, chemotactic response, and aromatic ring hydroxylating dioxygenases. An annotation analysis revealed that both genomes possessed non-ribosomal synthetase gene clusters for the lipopeptide synthetases srf and fen responsible for surfactin and fengycin production. Comparative studies of both genomes highlighted variability in gene operons mainly for surfactin biosynthesis.